Pembuatan Kopi Decaf dalam Kemasan Drip Bag dengan Metode Cold Brew di Rumah Kopi Ibu Bumi Banyuwangi - Istanti, Ari; Setiadevi, Shinta; Zazilah, Auda Nuril (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Rumah Kopi Ibu Bumi is a coffee house that processes roasted coffee and coffee brewing products. The method of brewing coffee at Rumah Kopi Ibu Bumi has been less practical, resulting in a thick, concentrated coffee body, relatively expensive products, and can only be enjoyed in one serving. This makes the process of brewing coffee inefficient and less economical. The cold brew method using drip bag coffee allows to solve this problem. This method results in a lower caffeine brew of coffee, can be used for several brews, and the product is more affordable. This program produces decaf coffee packaging products in drip bags that are ready to be marketed. This program was carried out well with the increasing of understanding and skills of business owners and employees in Rumah Kopi Ibu Bumi.